Pemahaman dan Preferensi Bahasa Masyarakat Indonesia pada Istilah Komputer dan Internet - Alfelia Nugky Permatasari; I Dewa Putu Wijana (JLA (Jurnal Lingua Applicata), 2018)
Technology, including computers and internet, cannot be separated from Indonesians. At the beginning of computers and internet existence in Indonesia, the government took an initiative to make computers and internet equivalent terms through Presidential Decree No. 2 Year 2001. This aimed to ease Indonesians in using computers and/or internet. This effort then generated “Senarai Padanan Istilah" consisting of 711 equivalents from 629 English terms. This study aims to investigate Indonesians’ comprehension, language preference, including their reason in choosing a particular language regarding computer and/or internet terms. The data were obtained from online questionnaire. The data obtained then were used to investigate Indonesians’ comprehension of the terms as well as their language preference relating to the computer and/or internet terms. The results are then presented descriptively. This research results in: 1) Indonesians have a fairly high understanding related to computer and/or internet equivalent terms; 2) however, Indonesians prefer English to bahasa Indonesia, as many as 91.9% of the respondents; 3) English preference by the  respondents is motivated by English terms familiarity, English terms ease to be understood, the lack of appropriateness of the equivalent terms, English shorter terms, and the unavailability of equivalent terms in the computer program they run.